2010
DOI: 10.1126/science.1194238
|View full text |Cite
|
Sign up to set email alerts
|

Bacteria Use Type IV Pili to Walk Upright and Detach from Surfaces

Abstract: A searchable database of images allows detailed analysis of bacterial motility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
187
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(201 citation statements)
references
References 7 publications
14
187
0
Order By: Relevance
“…The endocytosis of isolated protoplasts treated with 0, 30, or 80 μM LaCl 3 was observed using a total internal reflection fluorescence microscope (Olympus) with high spatial and temporal resolutions, as previously reported (26,27). Bright-field movies (∼30 images) were collected at one frame every 2 s using an Olympus microscope equipped with a 100× objective, as previously reported (26,27).…”
Section: Emarg Measurement Of Subcellular Distribution Of La(iii)mentioning
confidence: 99%
See 1 more Smart Citation
“…The endocytosis of isolated protoplasts treated with 0, 30, or 80 μM LaCl 3 was observed using a total internal reflection fluorescence microscope (Olympus) with high spatial and temporal resolutions, as previously reported (26,27). Bright-field movies (∼30 images) were collected at one frame every 2 s using an Olympus microscope equipped with a 100× objective, as previously reported (26,27).…”
Section: Emarg Measurement Of Subcellular Distribution Of La(iii)mentioning
confidence: 99%
“…Next, we used a new method established recently (26,27) to visualize the dynamic processes of endocytosis 12 h after the horseradish leaves were treated with 30 or 80 μM LaCl 3 . Movies S1-S5 were then made after the bright-field images of horseradish and Arabidopsis protoplasts were collected at one frame every 2 s using a total internal reflection fluorescence microscope.…”
Section: La(iii) Treatments Activated Endocytosis In Plant Cellsmentioning
confidence: 99%
“…In M. xanthus it has also been shown that the presence of pili at the poles is dynamically regulated through the localized activation of the assembly system (which itself has recently been shown to be stable and remain at both poles 29 ) and clustering of the PilT and PilB proteins, two antagonistic ATPases promoting pilus retraction and elongation, respectively 28 . In both species, the patterns of motion can be complex with several modes of pili-dependent motility in P. aeruginosa 30,31 and both pilidependent and pili-independent mechanisms of surface motility in M. xanthus 32 .…”
mentioning
confidence: 99%
“…Appropriate lower level processes include imaginative mechanisms of motility (demonstrated by bacteria that rise up and walk [26]), timing and vectors of movement and the physiology of hibernation and diapause. The panoply of influences modifying departure and settlement options available to, and decisions by, individuals represent another level associated with the mechanics of dispersal (electronic supplementary material, table S1).…”
Section: Mechanics: How Habitat Selection Workmentioning
confidence: 99%